Choreo-graphic figures : deviations from the line - Gansterer, Nikolaus; Cocker, Emma; Greil, Mariella (Berlin : De Gruyter, 2017)
"Choreo-graphic Figures: Deviations from the Line stages a beyond-disciplinary, inter-subjective encounter between the lines of choreography, drawing and writing, for exploring those forms of thinking-feeling-knowing produced through collaborative exchange, in the slippage and deviation, as different modes of practice enter into dialogue, overlap, collide. The publication is conceived as a studio-laboratory in itself, drawing together critical reflections and experimental practices that focus on the how-ness -- the qualitative-procedural, aesthetic-epistemological and ethical-empathetic dynamics -- within shared artistic exploration, directing attention to an affective realm of forces and intensities existing before, between and beneath the more readable gestures of artistic practice"--Publisher's website.
Also available as part of a 2-volume set, ISBN 978-3-11-055167-9.
Index on dust jacket.
Imported from: pulse.uta.edu:7099/pulse (Do not remove)
boek
Keywords: Arts -- Experimental methods; Arts -- Research; Artistic collaboration; Group work in art